Methylmercury in caddisflies and mayflies: Influences of water and sediment chemistry. (January 2022) - Clarke, Rachel G.; Klapstein, Sara J.; Hillier, N. Kirk; O'Driscoll, Nelson J.
Abstract: Quantifying methylmercury (MeHg) concentrations and uptake at the base of the food web is useful for assessing mercury exposure risk to higher trophic level organisms. Higher MeHg concentrations near the base of the food web may result in more MeHg exposure and accumulation in higher trophic organisms. Here, we analyze MeHg in caddisflies, mayflies, lake water, and sediment collected from two temperate lakes and one brook in Kejimkujik National Park, Nova Scotia, Canada. Overall, caddisfly larvae MeHg (15.38–276.96 ng/g; n = 29) was not significantly correlated with water chemistry. Whereas mayfly naiads MeHg (14.28–166.82 ng/g; n = 31) was positively correlated with water MeHg ( r s  = 0.43), negatively correlated with pH ( r s  = −0.49), and positively correlated with dissolved organic carbon (DOC; r s  = 0.48). Of the mercury in insect tissues, the %MeHg ranged from 56 to 75 % in caddisfly larvae and 38–47 % in mayfly naiads. MeHg bioaccumulation factors (BAF) varied greatly (water to tissue BAFs = 0.145 × 10 6 –1.054 × 10 6 ; sediment to tissue BAFs = 0.017 × 10 6 –0.541 × 10 6 ). This study highlights the importance of quantifying variations in MeHg bioaccumulation and BAFs of common aquatic insect bioindicators at the base of complex food webs. Graphical abstract: Image 1 Highlights: Mayfly MeHg was more influenced by water than sediment. Caddisfly larvae MeHg may be more influenced by sediment than water. Each invertebrate type had wide %MeHg ranges likely due to feeding ecology. Caddisflies and mayflies are good indicators of methylmercury loading to food webs. Adult caddisflies and mayflies efficiently transfer MeHg to terrestrial food webs.